Family of FLP Peptides in Caenorhabditis elegans and Related Nematodes - Li, Chris; Kim, Kyuhyung (Frontiers in Endocrinology, 2014)
Neuropeptides regulate all aspects of behavior in multicellular organisms. Because of their ability to act at long distances, neuropeptides can exert their effects beyond the conventional synaptic connections, thereby adding an intricate layer of complexity to the activity of neural networks. In the nematode Caenorhabditis elegans, a large number of neuropeptide genes that are expressed throughout the nervous system has been identified. The actions of these peptides supplement the synaptic connections of the 302 neurons, allowing for fine tuning of neural networks and increasing the ways in which behaviors can be regulated. In this review, we focus on a large family of genes encoding FMRFamide-related peptides. These genes, the flp genes, have been used as a starting point to identifying flp genes throughout Nematoda. Nematodes have the largest family of FMRFamide-related peptides described thus far. The challenges in the future are the elucidation of their functions and the identification of the receptors and signaling pathways through which they function.